Literature Review : Terapi Komplementer dalam Mengatasi Kecemasan Menjelang Persalinan Normal pada Ibu Primigravida - siska, deby utami (STIKES ADVAITA MEDIKA TABANAN, 2025)
Childbirth anxiety is a common experience for primigravida mothers, which can have a negative impact on their physical and psychological well-being. To overcome this anxiety, various complementary therapies have been developed and applied in clinical practice. This literature aims to explore the effectiveness of complementary therapies, such as music therapy, aromatherapy, meditation, autogenic relaxation techniques, and the butterfly hug method, in reducing anxiety in primigravida mothers approaching childbirth. Based on a review of recent research (2014–2024), the results show that complementary therapies can have a positive effect on reducing anxiety in pregnant women, with various mechanisms, ranging from sensory stimulation to regulating the body's stress response. Therapies such as lavender aromatherapy and relaxation music have been shown to be effective in creating a calming atmosphere, while mindfulness and autogenic techniques help increase body awareness and reduce anxiety responses. Although the results of this study show the great potential of complementary therapies, further research is needed to explore more personalized and evidence-based interventions. It is hoped that these findings can enrich the options for managing anxiety in primigravida mothers and support the implementation of more effective practices in the maternal health sector. Keywords: anxiety, primigravida mothers, complementary therapy, childbirth, aromatherapy, relaxation music, mindfulness.